Penguatan Ideologi Pancasila Dalam Kehidupan Mahasiswa - Suyono Suyono; Jihan Amelia Nadiul Fatriah; Bellatrix Nandayani; Winda Anggita Rini; Aulia Diamantha Nur Fitria; Dina Ayu Angraeni; Ihda Safira; Ahmad Naufal Syarif; Qurrota ‘Ayun Azzahro Nur Fauziah (Journal of Student Research, 2025)
Pancasila as a state ideology has a fundamental role in shaping the character of students as agents of change in society. This research aims to examine the application of Pancasila values in campus life and its impact on the formation of student character. The method used is literature study, by collecting and analyzing relevant literature, such as books, journals, articles, and documents related to Pancasila and higher education. The results of the study show that the application of the principles of equality, justice, and respect for diversity in the campus environment creates an inclusive and supportive atmosphere, encouraging students to respect differences, work together, and actively participate in decision-making. The values of cooperation, democracy, and appreciation for diversity are the basis for students to contribute to social development. In conclusion, strengthening the Pancasila ideology on campus not only strengthens the character of students, but also encourages them to play an active role in sustainable development and social change, while maintaining Indonesian national identity.